N-Acetylcysteine treatment of dystrophic mdx mice results in protein thiol modifications and inhibition of exercise induced myofibre necrosis - Terrill, J.; Crabb, Hannah; Grounds, M.; Arthur, P. (Elsevier Ltd, 2012)
Oxidative stress is implicated as a factor that increases necrosis of skeletal muscles in Duchenne Muscular Dystrophy (DMD) and thedystrophic mdx mouse. Consequently, drugs that minimize oxidative stress are potential treatments for muscular dystrophy. This studyexamined the in vivo benefits to mdx mice of an antioxidant treatment with the cysteine precursor N-acetylcysteine (NAC), administeredin drinking water. NAC was completely effective in preventing treadmill exercise-induced myofibre necrosis (assessed histologically) andthe increased blood creatine kinase levels (a measure of sarcolemma leakiness) following exercise were significantly lower in the NACtreated mice. While NAC had no effect on malondialdehyde level or protein carbonylation (two indicators of irreversible oxidative damage),treatment with NAC for one week significantly decreased the oxidation of glutathione and protein thiols, and enhanced muscleprotein thiol content. These data provide in vivo evidence for protective benefits of NAC treatment on dystropathology, potentiallyvia protein thiol modifications.